Answers

  • Brainly User
2015-12-28T10:32:41+08:00
Y = x² - 2x - 3

a) Equate the equation to 0 ⇒  y = 0
     x² - 2x - 3 = 0

b) Solve for the roots (x values) by factoring the quadratic equation:

Factors:
(x - 3) (x + 1) = 0

x - 3 = 0                                  x + 1 = 0
x - 3 + 3 = 0 + 3                     x + 1 - 1 = 0 - 1
x = 3                                       x = -1

ANSWERS:
1.)  The value of y is 0 (zero) at x-axis values  3 and -1.

2)  The graph, which is a parabola opening upwards (with vertex at minimum), intersects the x-axis at 3 and -1.
0